Particle Size Effect and Temperature Effect on the Pore Structure of Low-Rank Coal - Li, Teng (ACS Omega, 2021)
[Image: see text] High moisture content and high volatile content are typical characteristics of low-rank coal. To acquire the pore structure characteristics of low-rank coal accurately, the particle sizes and the pretreatment temperatures are two key parameters that should be considered when the low-pressure liquid-nitrogen adsorption is used. In this study, a low-rank coal sample was collected from Ordos Basin, and it was polished into four different particle sizes, 40–80 mesh, 80–120 mesh, 120–160 mesh, and 160–200 mesh, respectively. Besides, the low-rank coal samples are handled under seven various pretreatment temperatures (ranging from 120 to 300 °C); then, the pore structure characteristics of low-rank coal under various particle sizes and pretreatment temperatures are acquired. The dynamic change of pore volume and pore-specific surface area for low-rank coal is coincident. Under the same pretreatment temperatures, the mesopores’ volume continuously decreases. When the pretreatment temperature reaches 300 °C, a faint increase in their volume is observed. These results mean the mesopores are damaged during the progressive pulverization and heating procedures. When it comes to the same particle sizes, the mesopores’ volume also decreased with the increased pretreatment temperatures. Contrarily, the macropore volume is stable. This is mainly due to the decomposition of volatile matters and collapse of mesopores under the high pretreatment temperatures. However, the enrichment of ash in the mesopores could maintain the coal skeleton. The particle size effect and temperature effect mainly relate to the mesopores in low-rank coal, and the pores with the aperture below 5 nm contribute predominantly, followed by the pores with the aperture ranging from 5 to 10 nm.